(untitled) (Research, Society and Development, 2022)
Due to their therapeutic properties, plants are widely used by the population for medicinal purposes and for scientific studies regarding chemical constituents and pharmacological actions. As an example, we can mention the species Adenium obesum (Forssk.) Roem. & Schult. belonging to the Apocynaceae family and popularly known as desert rose. In traditional medicine this species is used to treat different venereal diseases such as gonorrhea and to treat wounds, infections, rhinitis, among other conditions. Because of this, this narrative aimed to describe the botanical, chemical and pharmacological aspects of the species. Thus, it was observed that the variety of chemical constituents of A. obesum includes the presence of cardiac glycosides, with approximately 50 phytochemicals belonging to the class of cardenolides, pregnanes, triterpenes and flavonoids. These are related to biological activities and can be seen as anticancer, antiviral, antibacterial, trypanocidal, acaricidal, molluscicidal, antioxidant and pesticidal activities. Therefore, this compilation of information on A. obesum shows the great importance of this species. However, further research is needed on the phytochemical components and biological activities performed with different parts of the species, since such components may have favorable potential in the incorporation of future pharmaceutical products.